The validity of the popular science book on Rubiaceae in the Special Purpose Forest Area of Lambung Mangkurat University - Hendra Hendra; Mochamad Arief Soendjoto; Bunda Halang (HAFECS PRESS, 2025)
Popular science books (PSB) on Rubiaceae in the Special Purpose Forest Area of ​​Lambung Mangkurat University (KHDTK ULM) are not available, let alone validated. PSB is a form of teaching material that supports critical thinking skills. This study aims to test the validity of the PSB on the Rubiaceae Family in KHDTK ULM as a learning resource in the Phanerogamae course. PSB contains 15 species of the Rubiaceae family as learning objects. The subjects were three experts (validators). They work as ULM lecturers and one of them teaches the Phanerogamae course. Validation was carried out on eight linguistic aspects with 14 assessment criteria. The average scores for the aspects of coherence (89.6%), readability (91.7%), use of vocabulary (100%), understanding of sentence meaning (83.3%), use of doubtful words (91.7%), application and implication (91.7%), use of definitions or explanations (83.3%), and other styles (83.3%). The PSB is categorized as highly valid and can be used as teaching material or a learning resource for the Phanerogamae course. Practicality and effectiveness tests are recommended to ensure the PSB is truly suitable for use. Abstrak. Buku sains popular (BSP) tentang Rubiaceae di Kawasan Hutan Dengan Tujuan Khusus Universitas Lambung Mangkurat (KHDTK ULM) tidak tersedia, apalagi tervalidasi. BSP merupakan salah satu bentuk bahan ajar yang mendukung keterampilan berpikir kritis. Penelitian ini bertujuan untuk menguji validitas BSP tentang Famili Rubiaceae di KHDTK ULM sebagai sumber belajar pada mata kuliah Phanerogamae. Buku ini mengandung 15 spesies famili Rubiaceae sebagai obyek pembelajaran. Subjeknya tiga ahli (validator). Mereka berprofesi sebagai dosen ULM dan salah satunya pengampu mata kuliah Phanerogamae. Validasi dilakukan terhadap delapan aspek kebahasaan dan 14 kriteria penilaian. Nilai rerata aspek koherensi (89,6%), keterbacaan (91,7%), penggunaan kosa kata (100%), pemahaman atas makna kalimat (83,3%), penggunaan kata-kata meragukan (91,7%), aplikasi dan implikasi (91,7%), penggunaan definisi atau penjelasan (83,3%), serta gaya lain (83,3%). BSP tersebut terkategori sangat valid, sehingga dapat digunakan sebagai bahan ajar atau sumber belajar pada mata kuliah Phanerogamae. Uji kepraktisan dan uji keefektifan direkomendasikan untuk dilaksanakan sehingga BSP tersebut benar-benar layak digunakan.